Ring Reconstruction on a Trichalcogenasumanene Buckybowl: A Facile Approach to Donor–Acceptor‐Type [5‐6‐7] Fused Planar Polyheterocycles. (5th November 2014) - Li, Xuexiang; Zhu, Yongtao; Shao, Jiafeng; Chen, Lichuan; Zhao, Sijie; Wang, Baolin; Zhang, Shangxi; Shao, Yongliang; Zhang, Hao‐Li; Shao, Xiangfeng
Abstract: The transformation of trichalcogenasumanene buckybowls into donor–acceptor‐type [5‐6‐7] fused polyheterocycles is disclosed. The strategy involves a highly efficient ring‐opening of the flanking benzene upon oxidation at room temperature, and facile ring closure by functional‐group transformation. Crystallographic studies indicate that the resulting [5‐6‐7] fused polyheterocycles possess a planar conformation owing to the release of ring strain by expansion of one of the six‐membered flanking rings to the seven‐membered one. Additionally, the [5‐6‐7] fused polyheterocycles bear electron‐withdrawing groups, which reduce the HOMO–LUMO energy gap, and display broad absorption bands extending to λ =590 nm. Consequently, these compounds show strong red emission with fluorescence quantum yields of up to 38 %. Abstract : ‐N‐ eingeschoben : Die Oxidation von elektronenreichen schalenförmigen Trichalkogenasumanenen mit Oxone bei Raumtemperatur resultiert in der hoch effizienten Öffnung eines der äußeren Benzolringe. Anschließend führt ein Ringschluss zu planaren Donor‐Akzeptor(D‐A)‐Polyheterocyclen mit [5‐6‐7]‐System und starker roter Emission.